Identification of gyrA Gene Resistance on Bacteria Escherichia coli and Klebsiellapneumoniaein Urinary Tract Infection Patients in Haji Adam Malik Center Hospital, Medan, Indonesia - Septiana, Lilik; Harahap, Urip; Ginting, Fransiscus (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: To find out whether Escherichia coli and Klebsiellapneumoniae that cause urinary tract infection have ciprofloxacin resistant gyrA coding genes. Interventions: The method used in this study is a cross sectional prospective design and carried out prospectively in urinary tract infection patients who have medical record data on the diagnosis urinary tract infection patients in the period February 2019 to January 2020 at the Haji Adam Malik General Hospital in Medan by takingurine from patients, then detected using Polymerase Chain Reaction (PCR) in the Integrated Laboratory of the Faculty of Medicine, Universitas Sumatera Utara. Main outcomes measure: The resistance coding gene in Escherichia coliwith the percentage of gyrA gene is 96,1% and Klebsiellapneumoniae has a low percentage where the expression of gyrA gene is 66,6%. Conclusion: The distribution of the gyrA gene in Escherichia coli is higher than that of Klebsiellapneumoniae.